ARAnimals: Mobile Application with Augmented Reality for the Learning of Vertebrate Animals - Pretell Cruzado, Johny (2021)
This work shows the results of an application of augmented reality for learning about vertebrate animals in preschool children. A mobile application with augmented reality, called ARAnimals, was implemented following the agile Scrum methodology. The research design was quasi-experimental, where the sample consisted of two classrooms of 5-year-old students from a private school in the city of Lima. The experimental group improved by 33.04% compared to the control group, which only improved by 14.56%. Furthermore, the difference in the average time it took to evaluate the subject in the experimental group and in the control group was significant. The time for the experimental group was 13.3 min., and the time for the control group was 16.7 min. It is concluded that the use of a mobile application with augmented reality satisfactorily influences the learning of vertebrate animals, specifically in four aspects that are included in the dimensions to which they correspond.